Aligning Governance in Structuring Policies for the Development of Pancasila ideology and National Resilience - Lutfi Trisandi Rizki; Bambang Soesatyo; Ma’ruf Cahyono (APPTHI, 2019)
The management of fostering the Pancasila ideology during the New Order era, which among other things, gave birth to a centralized government system, then the management of the Pancasila Ideology development by Badan Pembinaan Ideologi Pancasila (BPIP) must be rearranged so that Pancasila is truly actual in the life of society, nation, and state. In relation to the development of the Pancasila ideology, the formulation of the problem is how to arrange policies for the development of the Pancasila ideology to strengthen national resilience in terms of management aspects. Indonesia's national resilience is the dynamic condition of the Indonesian nation, which includes all aspects of integrated national life containing tenacity and resilience, which contains the ability to develop national strength in facing and overcoming all challenges, threats, obstacles, and disturbances coming from outside and from within. To ensure the nation's and state's identity, integrity, survival, and the struggle to achieve its national goals. Aspects of governance in structuring policies fostering Pancasila ideology on national security have a significant influence. Advances in information technology shape the character of the millennial generation, namely wanting to be fast, practical, to the point, and attached to social media. The inculcation of Pancasila values in the millennial generation must be done in a short, solid, and clear way using visual media. The millennial generation has advantages in understanding information technology and smart thinking logically, rationally, and critically. So, the relationship between the meaning of the precepts and operationalization must be logical and must be proven empirically. Abstrak Tata laksana pembinaan ideologi Pancasila pada masa orde baru yang antara lain telah melahirkan sistem pemerintahan yang sentralistis, maka tata laksana pembinaan Ideologi Pancasila oleh Badan Pembinaan Ideologi Pancasila (BPIP) harus ditata ulang sehingga Pancasila benar-benar aktual dalam kehidupan bermasyarakat, bserbangsa dan bernegara. Terkait dengan pembinaan Ideologi Pancasila, maka rumusan masalahnya adalah bagaimana penataan kebijakan pembinaan ideologi Pancasila untuk memperkokoh ketahanan nasional ditinjau dari aspek tata kelola atau governance. Ketahanan nasional Indonesia adalah kondisi dinamik bangsa Indonesia yang meliputi segenap aspek kehidupan nasional yang terintegrasi berisi keuletan dan ketangguhan yang mengandung kemampuan mengembangkan kekuatan nasional, dalam menghadapi dan mengatasi segala tantangan, ancaman, hambatan, dan gangguan, baik yang datang dari luar maupun dari dalam, untuk menjamin identitas, integritas, kelangsungan hidup bangsa dan negara, serta perjuangan mencapai tujuan nasionalnya. sAspek tata laksana dalam penataan kebijakan pembinaan ideologi pancasila terhadap ketahanan nasional mempunyai pengaruh yang signifikan. Kemajuan teknologi informasi membentuk karakter generasi millennial yakni ingin serba cepat, praktis, to the point, dan lekat dengan media sosial. Penanaman nilai-nilai Pancasila pada generasi millennial harus dilakukan dengan cara yang singkat, padat dan jelas serta menggunakan media visual. Generasi millennial memiliki keunggulan dalam memahami teknologi informasi, pintar berpikir logis, rasional, dan kritis. Maka hubungan makna sila dan operasionalisasi sila harus logis, dan harus terbukti secara empiris. Kata kunci: Aspek Pemerintahan, Penataan, Kebijakan, Ideologi Pancasila, Ketahanan Nasional